Toxicología forense como ciencia interdisciplinar de la investigación criminal (2016)
This research aims to clarify the facts behind criminal investigation presented on June the 20th at City of Pasto, Nariño, Colombia, in which was found a 21 year old lifeless man with the physical evidence and elements of material evidence such as substances in the body specifically in the mouth, outside with powder characteristics, and a letter in his right hand from a suicide feature, among others, which allowed us to determine the research technique to apply. Through the development of the work it will be applied forensic toxicology as the main technique of judicial investigation and criminology, which is the auxiliary discipline of the prosecuting body among others established in protocols and manuals of judicial police such as forensic photography and forensic surveying setting the scene, EF and EMP. This document contains useful information for national and international academic community about basic notions and procedures of forensic toxicology applied to the case of research, with the main concerning toxic substances which determine through a laboratory process the cause of death deceased. This is;; the scientific method applied to the particular case, which is the analysis and procedures carried out to identify the different substances evaluated and analyzed by examination of forensic toxicology carried out by experts who cast the results of the injuries and cause of death deceased